225Association between phytosterol consumption esophageal cancer risk. (2nd September 2021) - Liu, Xudong; Sun, Liping; Zhao, Wenjing
Abstract: Background: Phytosterols have anticancer effects and have been shown to inhibit various forms of cancer. However, epidemiological studies on the relationship between phytosterols and esophageal cancer risk are quite limited. The aim of this study was to investigate dietary phytosterol intake in relation to esophageal squamous cell carcinoma (ESCC) in the Chinese population. Methods: A case–control study was conducted from July 2011 to June 2013, recruiting 856 eligible ESCC cases plus 856 controls. Dietary information was collected by using a validated food frequency questionnaire. The OR and 95% CI of ESCC risk were assessed by multivariable logistic regression models. Results: The total phytosterols was found to be associated with a 56% (95% CI: 0.32- 0.61) reduction in ESCC risk when comparing the highest with the lowest tertiles, after adjusting for various confounders. An inverse association was also found between the consumption of β-sitostanol, β-sitosterol, campesterol and ESCC risk. No statistically significant association was found between rapesanol and ESCC risk. Conclusions: These data indicated that the consumption of total phytosterols,  β-sitostanol, β-sitosterol, campesterol is inversely associated with ESCC risk in a Chinese population Key messages: Phytosterols consumption may contribute to the prevention of esophageal squamous cell carcinoma